Psychometric analyses of the Bangla version of the Dark Triad Dirty Dozen - Ahmed, Oli (Heliyon, 2020)
Three undesirable social traits (Machiavellianism, psychopathy, and narcissism) collectively known as the‘Dark Triad’ have gained huge empirical attention during the past decades. The Dark Triad Dirty Dozen (DTDD) is a brief and psychometrically sound tool for assessing dark traits. In the present study, the psychometric properties of the DTDD-Bangla were assessed (n = 371) as there no information about its psychometric adequacy in the Bangladesh context. The item analysis results demonstrated that the DTDD-Bangla had good item discrimination indices in both CTT and IRT. The confirmatory factor analysis results supported the three factors first-order model in terms of model fits and items' factor loadings over the bi-factor model. Scale level analyses revealed that this scale and its subscales had good internal consistency reliabilities and composite reliability. The MGCFA supported scalar invariance between males and females. Overall, the DTDD-Bangla seems psychometrically sound measure to assess the dark traits and can be used in further researches in the Bangladesh context.